The Second Letter to the Thessalonians Re-read as Pseudepigraph1 - Andries van Aarde (HTS Teologiese Studies/Theological Studies, 2000)
The purpose of this study is to suggest a socio-historical frame of reference within which 2 Thessalonians may have communicated meaningfully with its intended readers. The question of the historical background of 2 Thessalonians is discussed within the context of the question of the letter's authorship. First, the article focuses on the traditional view that Paul was the author and that the delayed parousia was the issue he addressed. Second, the article aims to argue an alternative view: 2 Thessalonians is reread as a pseudepigraph and it is an open question whether the delayed parousia was really the problem the author addressed.